An Application of the Interactionist Perspective to the Study of Suicide Attempters - Easterday, Lois M. (1974)
At the Houston, Texas meeting of the American Association of Suicidology in April, 1973, a Houston criminologist threw out a challenge to the sociologists present. Since sociologists seem to be studying suicide as a form of deviance and studying deviance from the interactionist perspective, why, he asked, aren't sociologists studying suicide from the interactionist perspective? No-one present answered his question, and the challenge seemedto be ignored. In the months following the meeting this challenge became more and more intriguing. Therefore, I have chosen this opportunity to study suicide from the interactionist perspective